A qualitative exploration of the clinical presentation, trajectory, management and recovery of COVID‐19 in older people: Learning from frontline staff experiences. (13th August 2022) - Devi, Reena; Daffu‐O'Reilly, Amrit; Haunch, Kirsty; Griffiths, Alys; Jones, Liz; Meyer, Julienne; Spilsbury, Karen
Abstract: COVID‐19 had a devastating impact on older people living in care homes. This study explored the clinical trajectory and management of COVID‐19, as well as recovery of older people following infection during the early stages of the pandemic (May to August 2020). A two‐phase exploratory qualitative study was used. Frontline staff with experience of caring for older people with COVID‐19 were recruited to Phase 1, and senior care home operational and quality managers were recruited to Phase 2. During Phase 1 remote semi‐structured interviews ( n  = 35) were carried out with staff working in care homes, hospital and community settings in England. During Phase 2, a remote consultation event was carried out with senior care home operational and quality managers ( n  = 11) to share Phase 1 findings and check resonance, relevance and gaps. Data were analysed using Framework Analysis. Older people with COVID‐19 presented with wide ranging symptoms, and an unpredictable illness trajectory. The wide range of COVID‐19 symptoms required timely testing and supportive interventions. Staff used different interventions to manage symptoms and reported uncertainties of how individuals would respond. In care home settings, health and social care staff needed to work together when administering interventions such as subcutaneous fluids or oxygen therapy. Alongside symptom management, supportive care focused on nutrition and hydration, social interaction, and maintaining physical activity to meet both physical and emotional needs. The effects of prolonged periods of social isolation and inactivity on the health and well‐being of older people means rehabilitation is essential to enhance physical and emotional recovery, and to minimise impacts on cognition and function. The pandemic highlighted important areas for care of this population.